Please don't destroy [videorecording (Blu-Ray)] : the treasure of Foggy Mountain - Herlihy, Martin; Herlihy, Martin; Higgins, John, 1995-; Higgins, John, 1995-; Marshall, Ben, 1995-; Marshall, Ben, 1995-; Yang, Bowen, 1990-; Stalter, Meg; Mayo, X, 1987-; Sakura, Nichole, 1989-; Yarbrough, Cedric, 1973-; Mani, Sunita; et al. (Shout! Factory, 2025)
Three dead-beat co-workers fend off hairless bears, desperate park rangers and a hypocritical cult leader while searching for a priceless treasure.